Prototype Hand Sanitizer Otomatis Berbasis Arduino Dan Ultrasonik - Studi Kasus Di Stt Abdiel Ungaran - Ika Miranti; Bambang Suhartono (Jurnal Manajemen Informatika & Teknologi, 2021)
Currently in Indonesia there is a pandemic caused by the Corona Virus. The virus can cause disorders of the respiratory system to death. This virus is a new type of coronavirus that is transmitted to humans. The Corona virus can attack anyone and has spread rapidly to many countries, including Indonesia in just a few months. Abdiel Theological College (STT Abdiel) is one of the educational institutions in Ungaran that uses hand sanitizers to prevent the spread of the Corona virus. The hand sanitizer is still used manually, namely by holding it and pressing it. This does not guarantee the efforts to prevent the spread of the Corona virus. Therefore, a non-contact automatic hand sanitizer is needed in the campus environment.The purpose of this research is to make a prototype of a touchless automatic hand sanitizer based on the ultrasonic sensor HC-SR04 and arduino which is programmed using the C++ programming language with Arduino IDE software. In making this prototype, the researcher also uses a relay that is connected to a micro pump and hose which then sprays hand sanitizer automatically when a hand object approaches or is within the range of the ultrasonic sensor.The method used in making this automatic hand sanitizer prototype is the R&D (Research and Development) method. The result of the automatic hand sanitizer that has gone through validation testing by an expert and trials by users is that the prototype is able to spray hand sanitizer liquid automatically when the sensor detects an object. The automatic hand sanitizer prototype can be refilled easily, portable, and effective in minimizing the transmission of the Corona virus.